Tourism Demand and its Modelling - Salih, Bahram; Yasin , Ahmed (Humanities Journal of University of Zakho, 2021)
Tourism demand refers to consumers ’desire and ability to purchase different quantities of a tourism product at different prices during a certain period of time. By following the standard theory, the demand for tourism may be influenced by a myriad of price and non-price factors. And that tourism demand has four main types of elasticities, namely: the price elasticity of demand (the degree of response to changes in the price of that product itself), the income elasticity (the degree of response to changes in the level of consumer income), the cross elasticity (the degree of response to changes in the prices of alternative and complementary goods) and the flexibility of marketing / Advertising (the degree of responsiveness to changes in advertising expenditures on this product). Therefore, knowledge of price elasticity is important for tourism operators seeking to increase sales revenue. The literature contains a large number of research studies that attempt to model the factors that affect the tourist demand and the extent of this influence. In the case of estimating the application forms, careful attention must be paid to the model specifications, data collection, the functional formula, and evaluation of results.